Falls Are Associated With Decreased Autonomy, and Self-Efficacy Moderates This Relation: Results From a National Study - Hajek, André; König, Hans-Helmut (Frontiers in Psychiatry, 2019)
The first aim of this study was to examine the association between falls and perceived autonomy. The second aim was to investigate whether this association is moderated by self-efficacy. Cross-sectional data were drawn from the German Ageing Survey - a nationally representative sample of individuals living in private households aged 40 and above (n=7,746) in Germany. Perceived autonomy was quantified according to Schwarzer. Self-efficacy was assessed using a widely established scale by Schwarzer and Jerusalem. Adjusting for covariates, linear regressions revealed that experiencing a fall in the past 12 months was associated with lower perceived autonomy (β=-.09, p<.001). General self-efficacy moderated this association (β=.08, p=.02). Findings emphasized the association between falls and perceived autonomy as well as the moderating role of self-efficacy. Future longitudinal studies are required to gain insights into the temporal relationship between these variables.